Uji Aplikasi Kitosan Sebagai Edible Coating dalam Pengendalian Penyakit Antraknosa (Colletotrichum spp.) Pada Buah Pisang Cavendish (Musa acuminata L.) di Laboratorium - Erica Margaretha; Satriyo Restu Adhi (JURNAL PERTANIAN, 2026)
Anthracnose (Colletotrichum spp.) is a major postharvest disease that reduces the quality of Cavendish banana (Musa acuminatata L.) fruit. This study aims to evaluate the effect of chitosan application as an edible coating material on anthracnose disease of banana fruit, with a focus on symptom diameter and weight loss. The research was conducted in vitro at the Laboratory of Plant Disturbing Organisms, Faculty of Agriculture, Singaperbangsa University of Karawang, in November-December 2024, using a completely randomized design with five concentrations of 0%, 0.5%, 1%, 2%, and 3% chitosan, with five replications. The results showed that the application of 2% chitosan effectively suppressed the development of anthracnose disease symptoms, with an average symptom diameter of 2.77 cm and produced a percentage reduction in weight loss of 10.42%. Meanwhile, 3% chitosan concentration produced the best percentage of weight loss suppression, which was only 7.07%. In contrast, the control treatment showed the highest severity with a symptom diameter of 5.13 cm and a percentage of weight loss of 14.61%. These findings indicate that chitosan, especially at 2% concentration, is effective as an anthracnose control agent on Cavendish banana during storage